SOME ASPECTS OF THE IDENTIFICATION OF NUTRITIONALLY EFFICIENT SILKWORMS (INSECTA: LEPIDOPTERA: BOMBYCOIDEA), THEIR METABOLIC RATE AND SUSTAINABLE DEVELOPMENT AS ENERGY RESOURCES - NITU KUMARI; S. P. ROY (The Bioscan, 2011)
In the present investigation the nutritional efficiency of mulberry and tasar silkworms have been analysed. The tasar silkworms have highest activities in term of their relative rate of consumption (5.333g), assimilation (3.183g), growth (0.220g) and metabolism (2.963g) recorded in 4th larval stage. But their highest consumption rate (0.4907g/g/day), assimilation rate (0.3493g/g/day), growth rate (0.01730g/g/day) and metabolic rate (0.3319g/ g/day) was observed in 2nd larval stage. Interestingly in mulberry silkworm the maximum consumption, assimilation, growth and metabolism were measured in 3rd larval stage. The maximum values of consumption, assimilation, growth and metabolism were as 0.740g, 0.693g, 0.065g and 0.628g respectively. But their rates of consumption (0.162g/g/day), assimilation (0.1520g/g/day), growth (0.010g/g/day) and metabolism (1.405g/g/day) was found maximum in 1st larval stage. In mulberry silkworms the cocoon weight (1.480-1.731g), reelability (70%) and filament length (389m) was lesser than the tasar silkworm cocoon weight (7.61g-10.50g), reelability (80%) and filament length (683m). Thus, on the comparative basis the tasar silkworms have more metabolic rate and has more silk production capacity than the mulberry silkworms.